A Study on Intervention of Neurocognitive Skills for Primary School Students in Sivagangai Educational district - A. AdaikalaJeya, Dr. A. PioAlbina (International Journal of Advanced Science and Technology, 2020)
Neurocognitive skills are cognitive functions closely connected to the purpose of specific extents, neural pathways. Neurocognitive Skillsis a controlling device that affords the resources of knowledge, and goes well outside unassuming mock of others. The Skills are known the six dimensions. Literacy, Numeracy, Verbal Performance, Sensory motor Skills, Memory, Spatial Skills. The investigator used the simple random technique for this study. Ten schools in Sivagangai Educational District were randomly carefully chosen. Primary school students were selected from the above 10 schools. In total, the sample contained of 200 Primary school students. To find out the important difference of Neurocognitive Skills for Primary School Students.Keywords: Neurocognitive Skills, Primary School Students. Etc.